The Australian dictionary of accounting and finance terms - Godfrey, Jayne M. (Addison Wesley Longman Australia, 1997)
First published in 1983, this edition has been revised and updated to take into account all material current as at 1 September 1996. Godfrey is professor of accounting and finance at the University of Tasmania and Robb is senior lecturer at the University of Canterbury, NZ.